Analisis Brand Switching dan Penentuan Strategi Pemasaran Produk Bubble Tea Menggunakan Metode Markov Chain dan Game Theory - Anisa Nur Azizah; Rianita Puspa Sari (Universitas Teuku Umar, 2021)
The emergence of various kinds of food and drinks that are packaged and presented in an attractive manner has made a change in the culinary business into a lifestyle part. One of the culinary businesses that is becoming a trend is boba. Boba products with well-known brands can easily be found in urban areas. Karawang as one of the industrial cities in Indonesia is experiencing rapid business development trends. This causes business actors and owners of the boba beverage brand to prepare a strategy to anticipate brand shifting to customers. This study aims to determine the brand shift in customers of A products bubble tea and B products bubble tea which are one of the well-known brands of the boba business in Karawang, and to find out what strategies are appropriate so that business people can remain competitive and maintain customer loyalty. The use of the Markov Chain method to see the brand transfer to customers and the Game Theory method to find out strategies to win the competition. The results showed that the Market Share for A product bubble tea was 0.401 and the B product bubble tea was 0.599 with a business strategy that could be done, namely adding flavors at an affordable price.